Independent Assessment of the Quality of Russian Higher Education: What is the Point and What Can Be Improved - A. L. Drondin (Высшее образование в России)
An effective interaction between all stakeholders in the market of educational services is a necessary condition for improving the assessment of the quality of higher education, which, in turn, accentuates high relevance of studying the theory and practice of independent evaluation of higher education quality and quality assurance of educational programs. This is the main purpose of this publication, which is the result of the research in the field of independent evaluation and public accreditation of professional educational programs.During the examination of the projects on independent evaluation and professional and public accreditation of professional educational programs, the following methods were used: collection of empirical information, an analysis of official documents on quality assurance of education, generalization, interpretation.The article outlines a set of systemic problems hindering the process of formation of professional and public accreditation of professional educational programs launched in Russia and proposes the method of improving the independent evaluation and public accreditation of professional educational programs, which can be treated as a real leverage to improve the quality of domestic higher education.